Las Excepciones Dilatorias y Perentorias en el Juicio Civil Ordinario del Ecuador”. Necesaria Reforma. - Cunuhay Sigcha, Mónica Irene (2011)
To that legal contest, where the interests of the parties compete and includes a series of successive stages under the knowledge, direction and resolution of the Jurisdictional Body is what we call Civil Process, which from its early times determined that prosecutors, develop categories, inherent to it, with meanings that are used interchangeably in the actuality, but in no way contradicts its essence, that is why it is made necessary to analyze the theoretical and doctrinal aspects of the Civil Process Ecuadorian, based on the different exceptions that the sued within it.